Interaction of the State Traffic Safety Inspectorate and State Technical Supervision in the Execution of Administrative Punishment in the Form of the Deprivation of Driver's License - Sergei I. Koryts (Сибирское юридическое обозрение, 2017)
The problems arising in the performance of administrative punishments in the form of deprivation of the driver's license to drive vehicles are described. Effective ways of solving the problems arising in the framework of interaction of courts (judges), bodies of the State Traffic Safety Inspectorate and State Technical Supervision are suggested, in the exercise of their powers in the course of carrying out this activity.